Repeat Minimally Invasive Mitral Valve Replacement for Recurrent Mitral Stenosis after OMC in Patients Who Decline Blood Product Transfusion for Religious Reasons - Yujiro Ito; Yoshitsugu Nakamura; Osamu Tagusari; Shigehiko Yoshida (Case Reports in Surgery)
Cardiac surgery for Jehovah’s Witness (JW) patients is considered to be high risk because of patients’ refusal to receive blood transfusion. We report a successful mitral valve replacement for recurrent mitral stenosis after OMC with minimally invasive right thoracotomy, without any transfusion of allogeneic blood or blood products. This minimally invasive mitral valve replacement through right thoracotomy was an excellent approach for JW patients.